Drinking with parents: Different measures, different associations with underage heavy drinking?. Issue 6 (December 2017) - Pape, Hilde; Bye, Elin K.
Aims: Is drinking with parents (DWP) likely to curb or to encourage adolescent heavy drinking? The scant number of studies addressing this issue have arrived at contradictory conclusions, which may reflect that different measures of DWP have been used. We pursued the assumption, taking potential confounding related to parental alcohol-specific rule-setting and parenting style into account. Method: Data stem from the Norwegian 2015 ESPAD survey of 15–16 year olds. Drinking with parents at the last drinking event and the frequency of DWP in the past year were assessed among those who had consumed alcohol ( n = 1374). Severe drunkenness and binge drinking in the past month were the outcomes. Parental covariates were accounted for in Poisson regression models. Results: One in five (21%) had been drinking with their parents the last time they consumed alcohol, and this DWP measure was strongly and inversely related to both drunkenness and binge drinking. Adolescents who reported no DWP episodes in the past year (61%) and those who reported 1–2 such episodes (30%) barely differed with respect to the two outcomes. More frequent DWP (9%) was significantly associated with an increased risk of heavy episodic drinking, but the statistical impact on severe drunkenness was no longer significant when adjusting for parental covariates. Conclusions: Different measures of DWP were related differently to adolescent heavy drinking, indicating that studies based on DWP at the last drinking event are biased in favour of the view that adolescents may "learn" sensible drinking by consuming alcohol with their parents.